Evaporative Self-assembly of Ordered Complex Structures. - Lin, Zhiqun, 1972- (World Scientific, 2012)
The use of spontaneous self-assembly, as a lithographic tool and as an external field-free means to construct well-ordered and intriguing patterns, has received much attention due to its ease of producing complex, large-scale structures with small feature sizes. An extremely simple route to highly-ordered, complex structures is the evaporative self-assembly of nonvolatile solutes (e.g., polymers, nanoparticles, carbon nanotubes, and DNA) from a sessile droplet on a solid substrate. To date, a few studies have elegantly demonstrated that self-organized nanoscale, microscale, and hierarchically.